Analisis Kemiskinan Multidimensi di Kabupaten Lombok Timur - Subhan Purwadinata (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine multidimensional poverty in East Lombok Regency. The data analysis used in this research is multidimensional poverty calculation analysis. The results of the research show that East Lombok Regency, based on the calculation of the Multidimensional Poverty Index in East Lombok Regency, shows the results of calculating the value of IKM with the nutritional proportion of IKM RT with children under five being 18.6%. The prevalence of diseases that interfere with main work in East Lombok Regency in 2023 is 28.8 %. School enrollment rate in 2023 is 58.6 %. The expected length of schooling (AHS) in East Lombok Regency in 2023 is 11.8 years. The percentage of households with a floor area under 7.2 square meters per person in East Lombok Regency in 2023 is 9.2 %. The percentage of individuals in households who drink from unsuitable drinking water sources in East Lombok Regency in 2023 is 2.44 %. The percentage of individuals in households who use inadequate cooking fuel sources in East Lombok Regency in 2023 is 83.3 %. The percentage of individuals who do not have a birth certificate in East Lombok Regency in 2023 is 5.2 %, and finaly the percentage of households in East Lombok who did not use the internet during the last 3 months was 21.82%. This figure is higher than the national average of 10.29 %. The conclusion of this research is that based on the results of multidimensional poverty measurements to determine priorities for poverty management policies/programs